Volatility of copper prices and the effect of real interest rate changes - Duvhammar, Moa (2018)
The purpose of this thesis is to determine if the predictions of the theory of storage can explain the volatility of copper prices during the past two decades. The theory predicts that decreasing interest rates should reduce the volatility of commodity prices by encouraging the smoothing of short-run price swings caused by temporary shocks to supply and demand. In contrast, interest rates should have no effect on price volatility in the long-run as inventory smoothing cannot be used against persistent shocks. The theory is tested by estimating the volatility of copper spot and futures prices traded on the London Metal Exchange (LME) using the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model for the period of 1994 to mid-2017. The effect of real interest rates changes on the volatility of the prices is also examined. Temporary shocks are identified by movements in the time spread of the futures curve, calculated as the price difference between the 15- months’ contract and the spot contract. The volatility effect of persistent shocks is represented by fluctuations in long-term prices in terms of the 15-months’ and 27-months’ contracts.